ANALISA BIAYA OPERASI KENDARAAN (BOK) ANGKUTAN UMUM ANTAR KOTA DALAM PROPINSI RUTE PALU - POSO - Rahman, Rahmatang (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
The interurban public transportation within province is one of many public transportation types used tocarry passengers from one city to another within a province, operated accordingly to the time androute scheduled by a transportation company.The objectives of the research was to find out theamount of the vehicle operational cost (VOC) of the interurban within the province and to find outthe compatibility between the rate set by the government in this periode and the income received bythe public transportation operator or entrepreneur. The research was conducted by colleting primaryand secondary data gathered through some instruments questionnaire and interview surveys towardsthe public transportation entrepreneurs and some related institutions.The result shows that theoperational cost of each vehicle vary according to the vehicle’s brand and production year. Thevehicle operational cost is Rp. 229.372.412/year. And the vehicle operational cost is Rp.184.542.434/year. For the received income, it also varies according to the types of vehicle. For thepublic transportation as much Rp. 92.487.588,-/year. And for the income is as much Rp. 54.917.566,-/year.